2024
DOI: 10.3390/genes15040484
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Adiponectin in Autosomal Dominant Kidney Disease: Insight and Implications

Ersilia Nigro,
Marta Mallardo,
Maria Amicone
et al.

Abstract: Autosomal Dominant Polycystic Kidney Disease (ADPKD) is a common monogenic disorder characterized by renal cysts and progressive renal failure. In kidney diseases, adipose tissue undergoes functional changes that have been associated with increased inflammation and insulin resistance mediated by release of adipokines. Adiponectin is involved in various cellular processes, such as energy and inflammatory and oxidative processes. However, it remains to be determined whether adiponectin is involved in the concomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Cardiovascular abnormalities are common in patients with ADPKD, with hypertension being the most frequent finding, and are associated with a worse renal outcome [ 3 ]. Recently, we demonstrated that adiponectin could influence the clinical phenotype of ADPKD patients, and that to analyze the association between polymorphisms and ADPKD risk could potentially provide important insights into ameliorating kidney outcomes [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular abnormalities are common in patients with ADPKD, with hypertension being the most frequent finding, and are associated with a worse renal outcome [ 3 ]. Recently, we demonstrated that adiponectin could influence the clinical phenotype of ADPKD patients, and that to analyze the association between polymorphisms and ADPKD risk could potentially provide important insights into ameliorating kidney outcomes [ 28 ].…”
Section: Discussionmentioning
confidence: 99%